After Hume. Issue 4 (1st August 2014) - Porter Groff, Ruth
Abstract: Analytic metaphysics has taken a sharp turn away from Hume. Almost all at once, it seems, it has become acceptable - perhaps even fashionable - to believe in real causal powers. This is welcome news for those formerly lone metaphysicians who thought all along that Hume was wrong, but it is also good news for critical realists. The following is an introductory overview of some of the recent literature, via synopses (with commentary) of three anthologies and one monograph. I encourage critical realists to engage with this material, to the mutual benefit of critical realism and analytic philosophy alike.